Pengaruh Nostalgia Proneness terhadap Ad-evoked Vicarious Nostalgia Iklan Kodak Eastman pada Konsumen Indonesia - Prasetya, Nicolas; Gunawan, Theresia; Istiharini (Business Administration Department - Universitas Katolik Parahyangan, 2023)
Generation Z consumer interest in products and services that evoke feelings of nostalgia has grown since the COVID-19 pandemic took place. This is due to the social distancing policy which causes various psychological problems, such as; loneliness, anxiety, and depression. Nostalgia itself is believed to be a powerful antidote in overcoming this problem. This phenomenon is shown in one way or another in the rise of the analog photography trend, particularly through the boom in demand for Kodak films which are popular with Generation Z consumers who do not have personal references to nostalgic Kodak advertising content. Based on this research, it is proven that nostalgia proneness or consumers' tendency to feel nostalgic emotions will affect the intensity of nostalgic emotions generated through the nostalgic advertisements produced, even though they are historical in nature or they do not have personal experience with these advertisements. This research also proves that references and trends are one of the important factors for Generation Z consumers in Indonesia to have a strong tendency to feel nostalgia that is vicarious, especially in understanding the content of the Kodak advertisements they see.